2010
DOI: 10.1063/1.3308542
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rotation on the electrohydrodynamic instability of a fluid layer with an electrical conductivity gradient

Abstract: The electrohydrodynamic instability of a horizontal rotating fluid layer with a vertical electrical conductivity gradient is considered. An external electric field is applied across the fluid layer to induce an unstably stratified electrical body force. A linear stability analysis has been performed to study the effect of rotation on the onset of electrohydrodynamic instability in the fluid layer. Results show that the instability behaviors depend heavily on the boundary condition of bottom surface. In the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 23 publications
(34 reference statements)
0
27
0
Order By: Relevance
“…Smorodin [19] investigated the instability of convective liquid dielectric flow in the alternating field of a vertical capacitor with boundaries heated to different tem peratures. The EHD instability of a horizontal rotating fluid layer with a vertical electrical conductivity gradient is considered by Ruo et al [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Smorodin [19] investigated the instability of convective liquid dielectric flow in the alternating field of a vertical capacitor with boundaries heated to different tem peratures. The EHD instability of a horizontal rotating fluid layer with a vertical electrical conductivity gradient is considered by Ruo et al [20] .…”
Section: Introductionmentioning
confidence: 99%
“…A good account of thermal instability problems of a rotating viscoelastic fluid is given by Sharma and Rana [21] and Shivakumara et al [22], Rana and Jamwal [23], Chand and Rana [24] and Rana et al [25]. Ruo et al [26] studied the effect of rotation on the electrohydrodynamic instability of a fluid layer with an electrical conductivity gradient whereas Shivakumara et al [27] studied the electrohydrodynamic instability of rotation couple stress dielectric fluid layer and found that the effect of increasing AC electric field number is to increase the transfer of heat more effectively and hasten the onset of convection and rotation inhibits the onset of electrohydrodynamic instability.…”
Section: Introductionmentioning
confidence: 99%
“…Macroscopic alignment of nanofibers has been improved in the past using different methods including the use of a rotating mandrel collector (Matthews, Wnek, Simpson, & Bowlin, 2002;Shields, Beckman, Bowlin, & Wayne, 2004), a copper wire drum (Katta, Alessandro, Ramsier, & Chase, 2004), and conducting plates (Li, Wang, & Xia, 2003). Recently, a novel approach to controlling instability in electrospinning is suggested, and the technology is termed as magnetic electrospinning (He et al, 2008;Ruo, Chang, & Chen, 2010;Wu, Yu, He, & Wan, 2007;Yang, Lu, Zhao, & Jiang, 2007;Yang, Zhang, Zhang, & Nie, 2008). In the magnetic electrospinning process (Ruo et al, 2010), the current in the jet under the magnetic field, produces a centripetal force, i.e.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, a novel approach to controlling instability in electrospinning is suggested, and the technology is termed as magnetic electrospinning (He et al, 2008;Ruo, Chang, & Chen, 2010;Wu, Yu, He, & Wan, 2007;Yang, Lu, Zhao, & Jiang, 2007;Yang, Zhang, Zhang, & Nie, 2008). In the magnetic electrospinning process (Ruo et al, 2010), the current in the jet under the magnetic field, produces a centripetal force, i.e. the direction of the Ampere force is always towards the initial equilibrium point, leading to the shrinking of the radius of whipping circle.…”
Section: Introductionmentioning
confidence: 98%